PENENTUAN STRATEGI PROMOSI UNIVERSITAS BUDI DARMA MENGGUNAKAN ALGORITMA K-MEANS CLUSTERING - Silalahi, Natalia (TIN: Terapan Informatika Nusantara, 2020)
Budi Darma University is one of the Private Universities (PTS) in the city of Medan, which is inseparable from promotional activities every year. Promotional activities carried out by Budi Darma University use a large enough cost so that the promotion carried out is also expected to get maximum results. The success of the promotion can be seen from the large number of students enrolling in the new school year. A successful promotion can be seen from the promotion strategy used, determining the promotion strategy is not an easy job because it must consider several aspects. To help determine the promotion strategy at Budi Darma University can use data mining, where data mining can find a new pattern of stored data sets. One of the techniques used in data mining is clustering technique with the algorithm used is K-Means. By using the K-Means algorithm the results are divided into 3 clusters where in each cluster the results can be seen to determine the promotion strategy